Efficient transfer of genetic material into mammalian cells using Starburst polyamidoamine dendrimers. - Kukowska-Latallo, J F (1996)
Starburst polyamidoamine dendrimers are a new class of synthetic polymers with unique structural and physical characteristics. These polymers were investigated for the ability to bind DNA and enhance DNA transfer and expression in a variety of mammalian cell lines. Twenty different types of polyamidoamine dendrimers were synthesized, and the polymer structure was confirmed using well-defined analytical techniques. The efficiency of plasmid DNA transfection using dendrimers was examined using two reporter gene systems: firefly luciferase and bacterial beta-galactosidase. The transfections were performed using various dendrimers, and levels of expression of the reporter protein were determined. Highly efficient transfection of a broad range of eukaryotic cells and cell lines was achieved with minimal cytotoxicity using the DNA/dendrimer complexes. However, the ability to transfect cells was restricted to certain types of dendrimers and in some situations required the presence of additional compounds, such as DEAE-dextran, that appeared to alter the nature of the complex. A few cell lines demonstrated enhanced transfection with the addition of chloroquine, indicating endosomal localization of the complexes. The capability of a dendrimer to transfect cells appeared to depend on the size, shape, and number of primary amino groups on the surface of the polymer. However, the specific dendrimer most efficient in achieving transfection varied between different types of cells. These studies demonstrate that Starburst dendrimers can transfect a wide variety of cell types in vitro and offer an efficient method for producing permanently transfected cell lines.